Contemporary sociological thinkers and theories - Segre, Sandro (Ashgate, 2014)
This book offers a comprehensive overview of the major theoretical perspectives in contemporary sociology, covering schools of thought or intellectual movements within the discipline, as well as the work of individual scholars. The author provides not only a rigorous exposition of each theory, but also an examination of the scholarly reception of the approach in question, considering both critical responses and defences in order to reach a balanced evaluation. Chapters cover the following theorists and perspectives: Alexander Bourdieu Ethnomethodology Exchange Theory Foucault Giddens.